Jean Baptiste: A Story of French Canada - Le Rossignol, James Edward, 1866-; Curtis, Dora, 1875-1920 (Salt Lake City, UT : Project Gutenberg, 2013)
"Jean Baptiste: A Story of French Canada" by J. E. Le Rossignol is a novel written in the early 20th century. The narrative centers around Jean Baptiste Giroux, a young man wrestling with his vocation and identity within the societal expectations of his rural French-Canadian community. He faces the pressure to pursue the priesthood, a calling that he eventually rejects in favor of a different path. At the start of the book, we are introduced to Jean in a schoolroom setting, where he is encouraged by his teacher and the local priest, M. Paradis, to embrace a future as a priest. During a conversation between Jean and the curé, Jean expresses uncertainty about his vocation but is led to believe he possesses the necessary qualities for priesthood. Following a moment of introspection and a somewhat chaotic encounter with another student, Pamphile, it becomes clear that Jean's ambitions lie beyond the ecclesiastical life. The opening portion also provides glimpses of his family dynamics and foreshadows the deeper conflicts he will face as he seeks to define his place in the world. As the story unfolds, Jean s internal struggles are complemented by the vibrant backdrop of French-Canadian life, setting the stage for both personal and communal challenges. (This is an automatically generated summary.)
Release date is 2013-07-22
Produced by Al Haines
Keywords: Canada -- Fiction; French Canadians -- Fiction